2021
DOI: 10.3390/vaccines9050438
|View full text |Cite
|
Sign up to set email alerts
|

The Safe Baculovirus-Based PrM/E DNA Vaccine Protected Fetuses against Zika Virus in A129 Mice

Abstract: The Zika virus (ZIKV) is a mosquito-borne member of the Flaviviridae family of enveloped RNA viruses. The correlation between viral infection and fetal microcephaly was revealed in 2015, yet we still lack a vaccine against ZIKV. Here, we present a genetic vaccine that delivers the premembrane (prM) and envelope (E) genes of ZIKV using a recombinant baculovirus vector that expresses a human endogenous retrovirus (HERV) envelope on its surface to enhance gene delivery. We observed that baculoviruses with HERV en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…We had previously developed MERS-CoV, SARS-CoV2, and Zika virus vaccines using a baculovirus-based DNA vaccine (AcHERV) system (9, 12). Here, we demonstrated that AcHERV-COVID19D could be a potential SARS-CoV2 vaccine against pathogenic Delta and Omicron variants.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously developed MERS-CoV, SARS-CoV2, and Zika virus vaccines using a baculovirus-based DNA vaccine (AcHERV) system (9, 12). Here, we demonstrated that AcHERV-COVID19D could be a potential SARS-CoV2 vaccine against pathogenic Delta and Omicron variants.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the AcHERV system has been applied to develop a vaccine against Zika virus (AcHERV‐ZIKV), and AcHERV‐ZIKV induced the expression of high levels of IgG, neutralizing antibodies and IFN‐γ in mice. Moreover, AcHERV‐ZIKV conferred complete protection to IFN‐knockout (A129) female mice, pregnant mice and fetal mice challenged with ZIKV 76 . In addition to vaccine vectors, HERVs have also been used as vaccine adjuvants.…”
Section: The Roles Of Hervs In Therapymentioning
confidence: 99%
“…Moreover, AcHERV-ZIKV conferred complete protection to IFN-knockout (A129) female mice, pregnant mice and fetal mice challenged with ZIKV. 76 In addition to vaccine vectors, HERVs have also been used as vaccine adjuvants. Choi et al reported that female mice immunized with an inactivated influenza vaccine together with a murine granulocyte-macrophage colony-stimulating factor (GmCSF) gene delivered by the AcHERV system showed stronger humoural and cellular immune responses than mice immunized with the inactivated vaccine alone.Influenza-GmCSF-vaccinated mice were fully protected from lethal influenza virus challenge.…”
Section: Therapies Utilizing Herv Toolsmentioning
confidence: 99%
“…The focus of the global research and development efforts on designing, developing, and delivering safe and effective COVID-19 vaccine candidates should not undermine the continuing efforts to develop vaccines against other infectious diseases. Choi et al [ 7 ] explore the use of a recombinant baculovirus-vectored vaccine against Zika virus infection (ZIKV), demonstrating immunogenicity and protection in mice studies. The recombinant baculovirus vector is pseudo-typed with a human endogenous retrovirus envelope to enhance gene delivery of the premembrane and envelope genes of ZIKV, and the authors demonstrate immunogenicity and protection in mice studies.…”
mentioning
confidence: 99%